Analisis Kinerja Kiln dengan Menggunakan Campuran Batubara dan Sekam Padi Sebagai Bahan Bakar Alternatif pada Pabrik PT. Semen Tonasa - Muhammad Anshar; Yiyin Klistafani; Isdayanti Iskandar (Politeknik Negeri Ujung Pandang, 2021)
The cement industry is one of the energy intensive industries, because it absorbs a large amount of energy, and the kiln is the heart of the thermal energy system which is used as a place for combustion and clinker formation, therefore efforts are needed to determine the effect of using rice husk fuel on additional energy needed for combustion in the kiln and knowing the magnitude of the effect of adding rice husks on coal savings. This research was conducted to collect operational data of kiln which was obtained from the Central Control Room (CCR) Unit of Tonasa IV Factory of PT. Semen Tonasa. Data is taken directly on a computer which functions to regulate the operation of all production processes at the Tonasa IV Factory. The results of the analysis show that the use of rice husks has a relatively small effect on the energy produced when compared to without using rice husks. The addition of rice husk fuel does not show a significant effect on coal savings, but using rice husks can provide a calorific value of 3300 kcal / kg. In 1 kg of rice husk contains a calorific value of 3210 kcal / kg while in 1 kg of coal contains a heating value of 4910 kcal / kg, it can be seen that 1 kg of rice husk can replace approximately 1.53 kg of coal.